Fuzzy Analytic Hierarchy Process Based on Graphical Components - Walczuk, Michal; Karczmarek, Pawel (IEEE International Fuzzy Systems conference proceedings, 2021)
Many decision-making problems are solved using well-known Analytic Hierarchy Process (AHP). It is a tool to prioritize, rank, or choose from a set of alternatives. Also, its fuzzy version has been widely propagated and popular as well as still examined in a research community. However, practical application of the fuzzy AHP may bring some difficulties since a user (expert) should provide many values forming a membership function to precisely select a part of a range of a scale used in a pairwise comparison process. Moreover, using numerical or linguistic values can bring some limitation to the users, in particular, those who are not experienced with the scale. Therefore, in this paper, we present a comfortable approach to the fuzzy Analytic Hierarchy Process based on an application of a well-known Graphical User Interface programming component such as multirange slider. We thoroughly examine its application in contrast to other methods based on a numerical scale. In particular, we analyze the influence of an application of the multirange slider on the consistency of experts' opinions.